1982
DOI: 10.1149/1.2123765
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Temperature  K  ‐ TiS2 Cell

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Recently, Koch et al (10,11) showed that 2-methyltetrahydrofuran (2-MeTHF) was much less reactive toward Li than THF, and that higher Li cycling efficiency was obtained in 2-MeTHF containlng LiAsF~. Other ethers (or acetals) such as DME (12,13), 1,3-dioxolane (DOL) (12)(13)(14)(15), and polymethoxymethanes ( 16) have also been proposed as the solvents of secondary lithium cells. Sometimes mixed solvents have been used to improve solubility of electrolytic salts.…”
mentioning
confidence: 99%
“…Recently, Koch et al (10,11) showed that 2-methyltetrahydrofuran (2-MeTHF) was much less reactive toward Li than THF, and that higher Li cycling efficiency was obtained in 2-MeTHF containlng LiAsF~. Other ethers (or acetals) such as DME (12,13), 1,3-dioxolane (DOL) (12)(13)(14)(15), and polymethoxymethanes ( 16) have also been proposed as the solvents of secondary lithium cells. Sometimes mixed solvents have been used to improve solubility of electrolytic salts.…”
mentioning
confidence: 99%
“…From a specific energy point of view, batteries with insertion electrodes have the advantage that the overall cell process nM+ H ---> HMn [1] only includes a minimum of components, and no changes in overall electrolytic composition. The reaction at the positive electrode ~M + + ~e-+ HM~ ~ HM~+~ [2] is a topochemical reaction where the monovalent cation M + is inserted in the "host compound," H. 8 is an infinitesimal increment in the degree of insertion x and the compound HMx, for x ~< n, forms a single phase. Hence Eq.…”
mentioning
confidence: 99%
“…Hence Eq. [2] can take place in both directions with a minimum of structural changes. This should make it possible to design secondary batteries with long cycle life.…”
mentioning
confidence: 99%
“…As previously stated, studies of sodium intercalation in inorganic layered material started at the end of the 1980s, in conjunction with lithium ones. They were both referred to cathode materials, TiS 2 [196] and P2-Na x CoO 2 , [197,198] for which sodium intercalation was confirmed and quantified, as well as anode sodium-lead alloys. Prototypes of full sodium-ion cells were also assembled demonstrating surprisingly high cyclability for more than 300 cycles at an operational potential slightly lower than 3.0 V. Precisely this latter feature, did not particularly draw the attention if compared to high voltage LiCoO 2 /graphite systems.…”
Section: Cathode Materials For Sibsmentioning
confidence: 99%